Europe and Central Asia Economic Update, Spring 2020 : Fighting COVID-19 - World Bank (Washington, DC: World Bank, 2020)
In February 2020, the coronavirus outbreak interrupted the recovery that was underway in the Europe and Central Asia region earlier in the year. Given the rapidly evolving situation, this update summarizes the recent developments and growth outlook for the region under different scenarios regarding the outbreak. Although the magnitudes are uncertain, the pandemic is likely to derail the near-term outlook by interrupting daily activity, putting further downward pressure on commodity prices, disrupting tightly linked global and regional supply chains, reducing travel and tourist arrivals, and decreasing demand for exports from economies in the region. There are trade-offs between the health benefits of policies to slow down the spread of the disease and the economic costs of these actions. During these difficult times, it is important for policy makers to act decisively to save lives and invest in their public health systems; but also minimize the economic cost by strengthening the safety net for the most vulnerable; supporting the private sector through short-term credit, tax breaks, or subsidies; and being prepared to lower interest rates and inject liquidity to restore financial stability and boost confidence.